2012
DOI: 10.1177/0042085911433522
|View full text |Cite
|
Sign up to set email alerts
|

Caring in a Small Urban High School

Abstract: This article focuses on a small urban high school that developed a culture devoted to caring for their historically underserved students. Interviews with school founders, teachers, and alumni, as well as observations of classrooms and professional activities, revealed the high school attended to the affective needs of their students, which improved attendance and graduation rates, but often neglected to hold students to high academic standards, which led to future underperformance. The article concludes that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 17 publications
0
50
0
Order By: Relevance
“…For example, students are increasingly under pressure from forms of social activity that place them at risk, such as cyberbullying, gang membership and drug use (McCuaig, 2012;Muller, 2001). At the same time, students are pressurized to perform more resiliently, and within higher education, to more robust academic standards and with better progression outcomes of all kinds (Dallavis, 2014;Fitzmaurice, 2008;Rivera--McCutchen, 2012). In the context of higher education, such issues emerge as a battle for the soul of the student, with learning outcomes such as resilience, persistence and prevalence for example, frequently regarded as adjunct to the business of learning, and thus as 'soft' and optional but outcomes such as knowledge gained, or grades achieved, as 'hard' and thus more worthy (Zepke and Leach, 2010).…”
mentioning
confidence: 99%
“…For example, students are increasingly under pressure from forms of social activity that place them at risk, such as cyberbullying, gang membership and drug use (McCuaig, 2012;Muller, 2001). At the same time, students are pressurized to perform more resiliently, and within higher education, to more robust academic standards and with better progression outcomes of all kinds (Dallavis, 2014;Fitzmaurice, 2008;Rivera--McCutchen, 2012). In the context of higher education, such issues emerge as a battle for the soul of the student, with learning outcomes such as resilience, persistence and prevalence for example, frequently regarded as adjunct to the business of learning, and thus as 'soft' and optional but outcomes such as knowledge gained, or grades achieved, as 'hard' and thus more worthy (Zepke and Leach, 2010).…”
mentioning
confidence: 99%
“…Participation in career academies reduces high school dropout rates and increases high school completion rates (Brand, 2008;Castellano, Stone, Stringfield, Farley-Ripple, Overman, & Hussain, 2007;Farr et al, 2009;Hoachlander, 2008;Kemple, 2004;Kosine & Lewis, 2008;Mekinda, 2012;Stringfield et al, 2013). Likewise, students in small schools accumulate more credits, graduate at higher rates, demonstrate better attendance, and achieve higher test scores than students in larger high schools (Ancess & Allen, 2006;Barrow, Schanzenbach, & Claessens, 2015;Bloom & Unterman, 2013;Bloom & Unterman, 2014;Rivera-McCutchen, 2012;Schwartz, Stiefel, & Wiswall, 2013). Critical success factors found in the literature that are common to all three programs include socio-emotional support and community and a culture of high expectations and student engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In small schools, strong personal relationships have also been demonstrated to be key in providing academic benefits to students (Bloom & Unterman, 2013;Rivera-McCutchen, 2012). Ancess and Allen (2006) found that the implementation of a theme for a small school, similar to career focused academies, could be more engaging for students, improving their performance, allowing them to demonstrate achievement in multiple authentic ways, and creating a sense of community.…”
Section: Socio-emotional Support and Communitymentioning
confidence: 99%
See 2 more Smart Citations